Whole genome sequence and a phylogenetic analysis of the G8P[14] group A rotavirus strain from roe deer. Issue 1 (December 2017) - Jamnikar-Ciglenecki, Urska; Kuhar, Urska; Steyer, Andrej; Kirbis, Andrej
Abstract Background Group A rotaviruses (RVA) are associated with acute gastroenteritis in children and in young domestic and wild animals. A RVA strain was detected from a roe deer for the first time during a survey of game animals in Slovenia in 2014. A further RVA strain (SLO/D110–15) was detected from a roe deer during 2015. The aim of this study was to provide a full genetic profile of the detected RVA strain from roe deer and to obtain additional information about zoonotic transmitted strains and potential reassortments between human rotavirus strains and zoonotic transmitted rotavirus strains. The next generation sequencing (NGS) analysis on Ion Torrent was performed and the whole genome sequence has been determined together with a phylogenetic analysis. Results The whole genome sequence of SLO/D110–15 was obtained by NGS analyses on an IonTorrent platform. According to the genetic profile, the strain SLO/D110–15 clusters with the DS-1-like group and expresses the G8-P[14]-I2-R2-C2-M2-A3-N2-T6-E2-H3 genome constellation. Phylogenetic analysis shows that this roe deer G8P[14] strain is most closely related to RVA strains found in sheep, cattle and humans. A human RVA strain with the same genotype profile was detected in 2009 in Slovenia. Conclusions The G8P[14] genotype has been found, for the first time, in deer, a newly described host from the orderArtiodactyla for this RVA genotype. The finding of a rotavirus with the same genome segment constellation in humans indicates the possible zoonotic potential of this virus strain.